2023
DOI: 10.1002/crq.21399
|View full text |Cite
|
Sign up to set email alerts
|

The effects of moral exemplars awareness on common ingroup identification and reconciliation in post‐genocide Rwanda

Pauline Joy Atete,
Michał Bilewicz

Abstract: Moral exemplars (Imena) play an important part in commemorative practices and reconciliation in post‐genocide Rwanda. Acknowledging the essential role of moral exemplars in reconciliation and intergroup contact in post‐conflict setting, we aimed at examining the effects of exposure to moral‐exemplars on people's attitudes toward reconciliation and identification with superordinate national category in Rwanda. A study of 168 young Rwandans showed that higher awareness of moral exemplars during genocide was rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…At the same time, although moral exemplars have been often used in educational curricula in different countries (Bilewicz, 2007), there has never been a systematic analysis of the effects of such education. The current research by Atete and Bilewicz (2024) shows that exposure to such education has substantial effects on building a common ingroup identity, that in turn leads to more optimism about future reconciliation. Unfortunately, the effects of moral exemplars as an official narrative present in teaching curricula can have also paradoxical effects on reconciliation.…”
Section: New Research On Moral Exemplars: the Current Issuementioning
confidence: 91%
See 1 more Smart Citation
“…At the same time, although moral exemplars have been often used in educational curricula in different countries (Bilewicz, 2007), there has never been a systematic analysis of the effects of such education. The current research by Atete and Bilewicz (2024) shows that exposure to such education has substantial effects on building a common ingroup identity, that in turn leads to more optimism about future reconciliation. Unfortunately, the effects of moral exemplars as an official narrative present in teaching curricula can have also paradoxical effects on reconciliation.…”
Section: New Research On Moral Exemplars: the Current Issuementioning
confidence: 91%
“…After the violent phase of intergroup conflict, reconciliation processes are necessary to prevent future escalations of conflict (Noor et al, 2008). In a study conducted in Rwanda, we observed that awareness of moral exemplars increased national ties and led to more positive views of reconciliation among Hutu and Tutsi people (Atete & Bilewicz, 2024). In an intervention conducted in Bosnia, we found that prolonged exposure to moral exemplars elicited forgiveness, and this in turn increased belief in reconciliation among Bosniaks and Serbs (Čehajić‐Clancy & Bilewicz, 2017).…”
Section: Moral Exemplars In Eliciting Contact and Reconciliationmentioning
confidence: 99%
“…Another study found that ties with other members of a common national in-group mediated the effect of awareness of moral patterns on attitudes of reconciliation among people (Atete & Bilewicz, 2023). According to Harris and colleagues (2011), strength of ties was also positively associated with self-efficacy.…”
Section: Three Aspects Of Identification and Their Consequencesmentioning
confidence: 98%